Coblation Tonsillectomy Versus Blunt Dissectomy Tonsillectomy in Children - Matin, M A; Chowdhury, M Alamgir; Haque, Md Enamul; Islam, Md Nurul; Shamim, Tahsina; Muqeet, M A; Ali, Md Rowshan (Anwer Khan Modern Medical College Journal, 2013)
Tonsillectomy is one of the most common surgical procedure performed world wide by the ENT Surgeons.Various methods of tonsillectomy have been practiced over the century aimed at reducing or eliminating intraoperative and postoperative morbidity. Coblation tonsillectomy is a recently introduced surgical technique. Tonsillectomy over blunt dissection tonsillectomy in respect of operative time, intraoperative blood loss, postoperative pain, rate of healing of tonsillar fossa and other postoperative complications. This prospective randomized study was done at Maleka Nursing Home, Bogra and Bangladesh ENT Hospital, Dhaka for 36 months from 1st January 2008 to 31December 2010. 200 children were divided into two groups of equal number. In one group, the tonsillectomy performed by Coblation method and in the other group the tonsillectomy Age ranged from 3-12 years with mean age 5.6 in coblation group and 4-14 years with mean age 7.2 in dissection group. Number of male patients were slightly more than female with male female ratio was 3:2 in coblation group and 3.7:2 in dissection group. Operative time and amount of blood loss is significantly reduced in the coblation group (10-25 min, mean 12 min in coblation group, 18-35 min, mean 25 min in dissection group. Tonsillectomy by using coblation have shown less intraoperative bleeding (5ml-100 ml, mean 15 ml compared with 50-230 ml, mean 65 ml in dissection method).During post operative follow-up on day 8, children of coblation group experienced mild to moderate pain with maximum pain on day 2 and no pain on day 8. On the other hand dissection group experienced moderate to severe pain with maximum pain on day 4 and little or no pain on day 8.Children of coblation group returned to normal diet on day 3 and children of dissection group on day 8.On 8th post operative day, coblation group showed smooth healing without any granulation tissue in tonsillar fossa whereas granulation tissue is observed in dissection group. No major complications were noted in any group except one secondary haemorrhage in dissection group. Coblation tonsillectectomy offers less operative time, minimum blood loss, less post operative pain,early return to normal diet and rapid healing of tonsillar fossa. DOI: http://dx.doi.org/10.3329/akmmcj.v4i1.13681 AKMMC J 2013: 4(1): 25-29